Analysis of insulin pump settings in children and adolescents with type 1 diabetes mellitus. Issue 5 (22nd May 2015) - Lau, Yu Ning; Korula, Sophy; Chan, Albert K; Heels, Kristine; Krass, Ines; Ambler, Geoffrey
Abstract : Aim: To characterize current insulin pump settings used in young patients with type 1 diabetes mellitus (T1DM) and to assess their relationship to glycemic control. Methods: This retrospective study included patients aged <18 yr old with T1DM >1 yr using a Medtronic pump device. Pump data including number of blood glucose (BG) tests per day, basal and bolus insulin parameters, carbohydrate ratio (CR), and insulin sensitivity factors (ISFs) were averaged over 14 d for statistical analyses. Anthropometric data and recent glycosylated hemoglobin A1c (HbA1c) were recorded. Results: A total of 292 patients (144 males and 148 females) were included in the study. Participants had a median age (interquartile range, IQR) of 12.9 yr (10.0–15.1 yr) and pump duration of 2.8 yr (1.5–4.2 yr). No significant differences in median HbA1c (IQR) were observed in preschool [n = 14; HbA1c 7.8% (7.3–8.3%)], prepubertal [n = 105; HbA1c 8.1% (7.7–8.9%)], and adolescent subjects [n = 173; HbA1c 8.4% (7.7–9.0%)]. Adolescents took significantly fewer boluses and BG tests per day compared with younger children (p < 0.05). Age‐specific diurnal variation in basal insulin delivery was noted. Additionally, stronger carbohydrate cover and weaker corrections were used in real‐life compared with theoretical 500 and 100 rules, respectively. Lower HbA1c was associated with higher number of daily boluses, greater number of BG tests per day, lower average CR/500 rule ratio, and higher average ISF/100 rule ratio adjusted for age (R 2 = 0.22; p < 0.01). Conclusion: Insulin pump therapy requires continuous adjustments and glycemic targets are achieved by a minority. We believe this is the first study in pediatric cohort looking at association between CR and ISF with glycemic control.